Hungarian Monitoring, 15 October 1989 . [Magyar rádiófigyelő], 1989. október 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Territory leaders discuss lifting the Azerbaijani blockade of Karabakh - Raoul Wallenberg's relatives in the USSR Domestic Affairs: - Patriotic People's Front congress - Alliance of Young Democrats (Fidesz) congress - Hungarian Democratic Forum (MDF) economic debate forum - The question of presidential elections - László Rajk on the Alliance of Free Democrats (SZDSZ)'s election chances Economy: - Japanese financial assistance for Poland and Hungary - EEC customs allowance Külpolitika: - Hegyi Karabah azerbajdzsán blokádjának felszámolásáról tárgyaltak a területi vezetők - R. Wallenberg hozzátartozói a SZU-ban Belpolitika: - HNF kongresszus - FIDESZ kongresszus - MDF gazdasági vitafórum - Köztársasági elnökválasztás kérdése - Rajk László az SZDSZ választási esélyeiről Gazdaság: - Japán pénzügyi segélyt nyújt Lengyelországnak és Magyarországnak - EGK vámkedvezmény